Odpowiedzi

  • Użytkownik Zadane
2013-07-17T14:38:15+02:00

a)

(2a + b) ·c - (2ac - bc + 1) = 2ac + bc - 2ac + bc - 1= 2bc - 1


b)

5(x - z) + 2(z - x) = 5x - 5z + 2z - 2x = 3x - 3z


c)

2x²(x - 5) - 3x(x² - 3x + 5) = 2x³ - 10x² - 3x³ + 9x² - 15x = -x³ - x² - 15x


d)

6(a² + b + 1/3) - 6 (a² - ½)  - 3 (b + 1/3) = 6a² + 6b + 2 - 6a² + 3 - 3b - 1 = 3b + 4

1 5 1
2013-07-17T15:01:54+02:00

a)

2ac+bc-2ac+bc-1=2bc-1

b)

5x-5z+2z-2x=3x-3z

c)

2x³-10x²-3x³+9x²-15x=-x³-x²-15x

d)

6a²+6b+2-6a²+3-3b-1=3b+4